2008
DOI: 10.2337/db07-1285
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical and Alternating Infusions of Glucose and Intralipid in Rats Inhibit Insulin Gene Expression and Pdx-1 Binding in Islets

Abstract: OBJECTIVE—Prolonged exposure of isolated islets of Langerhans to elevated levels of fatty acids, in the presence of high glucose, impairs insulin gene expression via a transcriptional mechanism involving nuclear exclusion of pancreas-duodenum homeobox-1 (Pdx-1) and loss of MafA expression. Whether such a phenomenon also occurs in vivo is unknown. Our objective was therefore to ascertain whether chronic nutrient oversupply inhibits insulin gene expression in vivo. RESEARCH DESIGN AND METHODS—Wist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
81
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 41 publications
12
81
0
Order By: Relevance
“…In contrast, it is known that LC fatty acids can deplete insulin stores by promoting secretion of insulin while simultaneously inhibiting proinsulin synthesis (26,27). Additionally, multiple reports have documented the ability of excess lipid to inhibit insulin gene transcription both in vitro (28) and in vivo (29). It has also been recognized that culture in excess nutrients enhances basal secretion, which has been difficult to reconcile with the reduced maximal secretion.…”
mentioning
confidence: 83%
“…In contrast, it is known that LC fatty acids can deplete insulin stores by promoting secretion of insulin while simultaneously inhibiting proinsulin synthesis (26,27). Additionally, multiple reports have documented the ability of excess lipid to inhibit insulin gene transcription both in vitro (28) and in vivo (29). It has also been recognized that culture in excess nutrients enhances basal secretion, which has been difficult to reconcile with the reduced maximal secretion.…”
mentioning
confidence: 83%
“…In addition, we cannot exclude the possibility that alterations in glucose metabolism because of a HFHS-choice diet involve the 'toxic' effect of the combined increased levels of glucose and fatty acids on the pancreas (the so-called 'glucolipotoxicity' theory). 29 However, as the glucose elevations in HFHS-choice diet rats are much less than glucose concentrations necessary (twofold) to affect b-cell function, 30 it seems unlikely that the effect of the HFHS-choice diet involves glucolipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies of alternating 4-hour glucose (50%) infusions over a 72-hour period showed a total lack of effect of glucose on beta cell mass and proliferation in Wistar rats (Hagman et al, 2008), whereas, as mentioned above, continuous glucose infusion (20%) increased beta cell mass significantly after 48-hour in Sprague-Dawley rat . These results suggest considerations regarding infusion protocols, animal strains, dose-dependency, must be taken into accounts when comparing data between studies, and also their interpretations.…”
Section: The Dual Role Of Glucose In Beta Cell Survivalmentioning
confidence: 99%